2005
DOI: 10.1002/cbic.200400443
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Catalytic Domain of Inositol 1,4,5‐Trisphosphate 3‐Kinase A with Inositol Phosphate Analogues

Abstract: The levels of inositol 1,4,5-trisphosphate [Ins(1,4,5)P3] in the cytoplasm are tightly regulated by two enzymes, Ins(1,4,5)P3 3-kinase and type I Ins(1,4,5)P3 5-phosphatase. The catalytic domain of Ins(1,4,5)P3 3-kinase (isoenzymes A, B and C) is restricted to approximately 275 amino acids at the C-terminal end. We were interested in understanding the catalytic mechanism of this key family of enzymes in order to exploit this in inhibitor design. We expressed the catalytic domain of rat Ins(1,4,5)P3 3-kinase A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 50 publications
3
15
1
Order By: Relevance
“…In this case, the IC 50 and K i value are equivalent due to the low ATP concentrations in the assay. The K i of 18 M (Table 1) is somewhat higher than the values reported by other authors (21,22).…”
Section: Tnp Is a Selective Inhibitor Of The Ip6ks In Vitro And In Vivo-contrasting
confidence: 55%
“…In this case, the IC 50 and K i value are equivalent due to the low ATP concentrations in the assay. The K i of 18 M (Table 1) is somewhat higher than the values reported by other authors (21,22).…”
Section: Tnp Is a Selective Inhibitor Of The Ip6ks In Vitro And In Vivo-contrasting
confidence: 55%
“…Indeed, several groups have identified small-molecule ITPK inhibitors. Some show high ITPK-selectivity over IPMK33, 109112.…”
Section: Therapeutic Relevancementioning
confidence: 99%
“…18 F-FDMCI-3′-phosphate is not a substrate for the inositol transporter, and being very polar, cannot cross the cell membrane, and thus will be trapped inside the cell. 14 …”
Section: Resultsmentioning
confidence: 99%
“…11 More recently, Poinas et al studied the interaction of the catalytic domain of IP 3 -3KA with several inositol phosphate analogues and found that removal of the 2′-OH was tolerated and would still allow for substrate activity. 12 …”
Section: Introductionmentioning
confidence: 99%